Peramalan Penjualan Usaha Tahu Anyar di Kota Banjarbaru - Rudy Firmansyah; Luki Anjardiani (AGRIDES: Jurnal Agribisnis Perdesaan, 2014)
The objectives of the research were to analyze the market growth, market share, and sales forecasting of tofu company, to find out the condition of tofu company, and to find out the problems faced in the tofu company. The market growth of tofu company for 2009 until 2012 were 9,69 %, 9,09 %, -28,97 %, -11,76 %. The market share of tofu company for 2008 until 2012 were 12 %, 12,88%, 14,05%, 23,64%, 17,32%. The sales forecasting of tofu company for 2013 and 2014 were 271,67 ton and 244,78 ton. According to the Grand Strategy Matrix, the conditon of tofu company was good position. The result indicates that the condition of market growth and market share for 2009 and 2010 were in Quadrant I, then the condition of market growt h and market share for 2011 and 2012 were in Quadrant IV. The problem in the tofu company was slowmoving of soybean commodity by distributors. The slow moving of soybean influencing by the condition of climate in the main source of the soybean production place.